Authenticity in and through teaching in higher education : the transformative potential of the scholarship of teaching - Kreber, Carolin (Abingdon, Oxon : Routledge, 2013)
'Almost a quarter-century after the Carnegie report, Scholarship Reconsidered, the scholarship of teaching remains a contested idea, celebrated by some and critiqued by others. This new book is particularly relevant now however as it explores the notion of the scholarship of teaching through the lens of authenticity, a complex, intriguing and particularly striking and distinctively helpful notion which has caught the attention of several authors in adult and higher education. However, those writing about authenticity do not always make explicit what it is that they mean by this notion, nor are they clear about the philosophical foundations underpinning it. In developing the notion of the scholarship of teaching as an'authentic practice', the author draws on several complementary philosophical ideas to explore the nature of this practice, why it is imperative for universities to engage in it, what meaningful engagement wold look like and the conditions under which it might qualify as'authentic'. Core constructs employed include practice virtue communicative action'being','power', critical reflection and transformationThe scholarship of teaching is described as a practice sustained through critical reflection and critical self-reflection. Being a scholar of teaching is viewed as an ongoing transformative learning process, a process of becoming authentic, the latter ultimately aimed at both helping students to become authentic and creating a better world in which to teach, learn and live. Although explored as a practice in its own right, the scholarship of teaching is seen to be strengthened by being situated within a wider integrated notion of academic practice. The book combines the author's previous research on authenticity with earlier work on the meaning of the scholarship of teaching, offering a provocative, fresh and timely perspective on the scholarship of teaching and professional learning in our times but also providing guidance on how to create a better world in which to learn, teach and live'--
'What does it mean to be authentic? Why should it matter whether or not we become more authentic? How might authenticity inform and enhance the social practice of the scholarship of university teaching and, by implication, the learning and development of students? Authenticity in and through Teaching introduces three distinct perspectives on authenticity, the existential, the critical and the communitarian, and shows what moving towards greater authenticity involves for teachers and students when viewed from each of these angles. In developing the notion of'the scholarship of teaching as an authentic practice', this book draws on several complementary ideas from social philosophy to explore the nature of this practice and the conditions under which it might qualify as'authentic'. Other concepts guiding the analysis include'virtue','being','communicative action','power','critical reflection' and'transformation'. Authenticity in and through Teaching also introduces a vision of the scholarship of teaching whose ultimate aim it is to serve the important interests of students. These important interests, it is argued, are the students' own striving and development towards greater authenticity. Both teachers and students are thus implicated in a process of transformative learning, including objective and subjective reframing, redefinition and reconstruction, through critical reflection and critical self-reflection on assumptions. It is argued that, in important ways, this transformative process is intimately bound up with becoming more authentic'--
Includes bibliographical references (p. [175-191) and index.
Keywords: College teaching -- Philosophy; Authenticity (Philosophy)